Pelayanan Penanganan Penunggak Iuran BPJS Bagi Peserta JKN-KIS Kesehatan di Kantor Cabang Kota X - Dedi Prayitno (Jurnal Bisnis, Manajemen, dan Akuntansi, 2023)
Weak regulation of sanctions for BPJS participants regarding the obligation of contributions, BPJS for health resulted in a budget deficit. Projected budget deficit in 2018, the deficit will be Rp. 28.5 trillion. The expansion projection comes from diverting the 2018 deficit plus the burden of paying hospital bills since the beginning of 2018. BPJS Kesehatan finance director Kemal Imam Santoso said the company still has a carry over financial deficit of Rp. 9.1 trillion from last year. Based on the description of the discussion above regarding job descriptions on billing and finance, obstacles in billing JKN-KIS participant contributions, and efforts to handle participants who are in arrears at the Health Social Security Administering Body for City X branch offices Data and information is carried out by observing in the field of finance and billing by gathering information based on interviews, data review and existing financial / billing data. Observations made were 8 Billing and Finance staff at the BPJS Kesehatan City X branch office, having different but very related tasks starting from the Head of Billing and Finance who is fully responsible for staff performance and the smooth payment of participant contributions, two Staff participant contribution collection workers Billing is always attempted by contacting the company to find out the active status of participants by visiting, via WA, email or with JKN cadres. Sending the latest information regarding contribution payments, for example with REHAB to make it easier for participants. As well as developing the REHAB program. Meanwhile, there are 83,585 participants in BPJS Kota X Branch Offices who have arrears at the BPJS Kota X Branch Office until 2020 reaching Rp. 72,678,386,206. The need for employee job disks that are more specific and reliable considering the constraints of Covid 19 also have quite an effect on the contributions of independent participants, Keywords: dues; bills; arrears; billing; treatment